European Consensus Guidelines on the Management of Respiratory Distress Syndrome-2016 Update - ÖZEK, EREN (KARGER, 2017)
Advances in the management of respiratory distress syndrome (RDS) ensure that clinicians must continue to revise current practice. We report the third update of the European Guidelines for the Management of RDS by a European panel of expert neonatologists including input from an expert perinatal obstetrician based on available literature up to the beginning of 2016. Optimizing the outcome for babies with RDS includes consideration of when to use antenatal steroids, and good obstetric practice includes methods of predicting the risk of preterm delivery and also consideration of whether transfer to a perinatal centre is necessary and safe. Methods for optimal delivery room management have become more evidence based, and protocols for lung protection, including initiation of continuous positive airway pressure and titration of oxygen, should be implemented from soon after birth. Surfactant replacement therapy is a crucial part of the management of RDS, and newer protocols for surfactant administration are aimed at avoiding exposure to mechanical ventilation, and there is more evidence of differences among various surfactants in clinical use. Newer methods of maintaining babies on non-invasive respiratory support have been developed and offer potential for greater comfort and less chronic lung disease. As technology for delivering mechanical ventilation improves, the risk of causing lung injury should decrease although minimizing the time spent on mechanical ventilation using caffeine and if necessary postnatal steroids are also important considerations. Protocols for optimizing the general care of infants with RDS are also essential with good temperature control, careful fluid and nutritional management, maintenance of perfusion and judicious use of antibiotics all being important determinants of best outcome. (C) 2016 S. Karger AG, Basel
Keywords: Antenatal steroids; Continuous positive airway pressure; Evidence-based practice; Hyaline membrane disease; Mechanical ventilation; Nutrition; Oxygen supplementation; Patent ductus arteriosus; Preterm infant; Respiratory distress syndrome; Surfactant therapy; Thermoregulation; EXTREMELY PRETERM INFANTS; POSITIVE AIRWAY PRESSURE; INHALED NITRIC-OXIDE; BIRTH-WEIGHT INFANTS; INVASIVE SURFACTANT THERAPY; RANDOMIZED CONTROLLED-TRIAL; OXYGEN-SATURATION TARGETS; PLACEBO-CONTROLLED TRIAL; UMBILICAL-CORD MILKING; CHRONIC LUNG-DISEASE